2005
DOI: 10.1007/s00425-005-0195-7
|View full text |Cite
|
Sign up to set email alerts
|

Changes in chloroplast DNA during development in tobacco, Medicago truncatula, pea, and maize

Abstract: We examined the DNA from chloroplasts obtained from young and fully expanded leaves of tobacco (Nicotiana tabacum L.), Medicago truncatula, pea (Pisum sativum L.), and maize (Zea mays L.). The changes in plastid DNA content and structure were monitored by four independent methods: 4',6-diamidino-2-phenylindole (DAPI) staining with intact chloroplasts, in situ DAPI staining of cytological sections, ethidium bromide staining at the single-molecule level after exhaustive deproteinization of lysed chloroplasts, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
101
3
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(109 citation statements)
references
References 28 publications
4
101
3
1
Order By: Relevance
“…Our findings cannot be reconciled with those of Bendich and coworkers, who have claimed that ptDNA sharply declines or even vanishes completely from chloroplasts long before the onset of senescence in several species, notably including Arabidopsis and maize Rowan et al, 2004Rowan et al, , 2009Oldenburg et al, 2006;Shaver et al, 2006). The reasons for these differences are not entirely clear, but in our opinion, the reported findings are not conclusive because of artifact-prone methods and the lack of appropriate controls checking the biochemistry used.…”
Section: Ptdna Is Ontogenetically Stablecontrasting
confidence: 92%
See 2 more Smart Citations
“…Our findings cannot be reconciled with those of Bendich and coworkers, who have claimed that ptDNA sharply declines or even vanishes completely from chloroplasts long before the onset of senescence in several species, notably including Arabidopsis and maize Rowan et al, 2004Rowan et al, , 2009Oldenburg et al, 2006;Shaver et al, 2006). The reasons for these differences are not entirely clear, but in our opinion, the reported findings are not conclusive because of artifact-prone methods and the lack of appropriate controls checking the biochemistry used.…”
Section: Ptdna Is Ontogenetically Stablecontrasting
confidence: 92%
“…It was concluded that, in fully expanded leaves, most chloroplasts contain no or only insignificant amounts of DNA long before the onset of leaf senescence Rowan et al, 2004;Oldenburg et al, 2006;Shaver et al, 2006;Rowan et al, 2009). Retention of ptDNA was proposed to be dispensable after the photosynthetic machinery was established in that the plastome-encoded photosynthesis genes were no longer needed in adult leaves.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2). Because organelle DNA copy number changes during leaf cell differentiation (Baumgartner et al, 1989;Shaver et al, 2006), we sampled different developmental stages by taking advantage of the developmental gradient in the leaves of maize seedlings (Leech et al, 1973). The second leaf of seedlings at the early three-leaf stage was divided into basal, middle, and apical sections (Fig.…”
Section: Maize Locus W2 (Grmzm2g480171) Encodes a Chloroplast Dna Polmentioning
confidence: 99%
“…It is generally agreed that the ratio of chloroplast to nuclear gene copy number decreases as leaf cells mature, although the magnitude of this decrease has been a subject of debate (Baumgartner et al, 1989;Oldenburg and Bendich, 2004a;Rowan et al, 2004;Li et al, 2006;Shaver et al, 2006;Zoschke et al, 2007;Rowan et al, 2009).…”
mentioning
confidence: 99%